The relationship between customer satisfaction with customer services and store image toward supermarket : a case study in Sibu - Wong, Souk Ping (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The main objective of this study was to investigate the relationship between customer satisfaction with customer services and store image towards supermarket in Sibu. Data were collected from the 150 respondents who have visited the supermarkets in Sibu through questionnaire survey tool. The collected data were analyzed by using Statistical Package for Social Sciences (SPSS) Version 15.0. The pilot test and pre-test were carried out to assess the face validity of the questionnaire. Cronbach's Alpha was used to measure the reliability of the questionnaire. Furthermor:e, Descriptive analysis, Pearson correlation coefficient analysis and regression analysis were used to evaluate the relationships between the variables. The result showed that only one variable which is store facilities was positive correlated and has significant relationship to customer satisfaction. Therefore, this study is this study is important to reflect on the current supermarket retail activities in Sibu in order to enhance their store facilities, satisfy their customers and stay ahead of the retailing industry competition in Sibu.